Cystobactamid 507: Concise Synthesis, Mode of Action, and Optimization toward More Potent Antibiotics. Issue 32 (28th April 2020) - Elgaher, Walid A. M.; Hamed, Mostafa M.; Baumann, Sascha; Herrmann, Jennifer; Siebenbürger, Lorenz; Krull, Jana; Cirnski, Katarina; Kirschning, Andreas; Brönstrup, Mark; Müller, Rolf; Hartmann, Rolf W.
Abstract: Lack of new antibiotics and increasing antimicrobial resistance are among the main concerns of healthcare communities nowadays, and these concerns necessitate the search for novel antibacterial agents. Recently, we discovered the cystobactamids—a novel natural class of antibiotics with broad‐spectrum antibacterial activity. In this work, we describe 1) a concise total synthesis of cystobactamid 507, 2) the identification of the bioactive conformation using noncovalently bonded rigid analogues, and 3) the first structure–activity relationship (SAR) study for cystobactamid 507 leading to new analogues with high metabolic stability, superior topoisomerase IIA inhibition, antibacterial activity and, importantly, stability toward the resistant factor AlbD. Deeper insight into the mode of action revealed that the cystobactamids employ DNA minor‐groove binding as part of the drug–target interaction without showing significant intercalation. By designing a new analogue of cystobactamid 919‐2, we finally demonstrated that these findings could be further exploited to obtain more potent hexapeptides against Gram‐negative bacteria. Abstract : Optimized cystobactamid antibiotics : MedChem optimization of the antibiotic cystobactamid 507 targeting DNA gyrase resulted in the construction of analogues with improved activity. Bioactive conformation was disclosed and the shortest synthetic route established. Mode of action studies revealed specific binding at the DNA minor groove. Incorporation of a tripeptidic cystobactamid 507 analogue into a hexapeptide resulted in superior activity.